The translator as the other: Reflections of pre-service teachers of English and Portuguese about translation as a profession - Kirsch, William (BELT - Brazilian English Language Teaching Journal, 2020)
This paper presents a reflection and discussion upon a pedagogical project carried out in a class of Portuguese and English Languages at a Teacher Certification degree in a university in southern Brazil. In this project, students – future English teachers – had lectures with a variety of professional in the area of Languages: a public school teacher, a private language schoolteacher and a public translator. After each lecture, students wrote reflective essays about it to be read and discussed in class. This article focuses, therefore, on the essays produced by four of them after the lecture with the translator. It is possible to state that participants shift from an idealized view regarding translation to a more realistic one (that of a professional doing technical work). In the end, participants suggest this was an important reflection upon their professional future, which may not include teaching.